2023
DOI: 10.1093/humrep/dead008
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal remodelling of the composition and architecture of the human ovarian cortical extracellular matrix duringin vitroculture

Abstract: STUDY QUESTION How does in vitro culture alter the human ovarian cortical extracellular matrix (ECM) network structure? SUMMARY ANSWER The ECM composition and architecture vary in the different layers of the ovarian cortex and are remodelled during in vitro culture. WHAT IS KNOWN ALREADY The ovarian ECM is the scaffold within which follicles and stromal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 80 publications
0
13
1
Order By: Relevance
“…However, possible differences in the viscoelastic behaviour of the ovarian tissue and the mock wax may indeed bias the strain estimates that have been obtained. Another source of bias is the wide variations in tissue structure ( van Wezel and Rodgers, 1996 ; Grosbois et al, 2023 ) and mechanical behaviour from tissue donor to donor and from different harvesting zones of the same ovary. For the sake of an example, the Young’s modulus of the ovarian cortex has been reported to vary by as much as two orders of magnitude in different zones of the same ovary (Stewart et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, possible differences in the viscoelastic behaviour of the ovarian tissue and the mock wax may indeed bias the strain estimates that have been obtained. Another source of bias is the wide variations in tissue structure ( van Wezel and Rodgers, 1996 ; Grosbois et al, 2023 ) and mechanical behaviour from tissue donor to donor and from different harvesting zones of the same ovary. For the sake of an example, the Young’s modulus of the ovarian cortex has been reported to vary by as much as two orders of magnitude in different zones of the same ovary (Stewart et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites enter gluconeogenesis via the tricarboxylic acid cycle (TCA) cycle, while Hypro is an abundant constituent of collagen and elastin [ 28 ], which are the major components of the extracellular matrix (ECM) [ 29 ]. ECM, such as collagen, has important roles in folliculogenesis [ 30 ] and is altered in human ovarian cortical strips during culture [ 31 ]. Collagen (type IV) is known to be expressed in primordial to antral follicles in mice [ 32 , 33 ], humans [ 34 , 35 , 36 ], and cattle [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Del Valle and colleagues reported a significant increase in collagen IV in the stromal compartment of human ovarian cortex tissue cultured for 8 days, indicating that the ovarian cortex became more fibrotic during culture [51]. By contrast, Groibos and colleagues reported that human ovarian cortex tissue cultured for 6 days showed decreased collagen and increased elastin deposition [65]. This discrepancy may have resulted from differences in either the culture protocols or the donor material used.…”
Section: Ecm Deposition and Fibrosismentioning
confidence: 99%